Relationship between shift work and age-related macular degeneration: a cross-sectional analysis of data from the 5th Korea National Health and Nutrition Examination Survey (2010–2012) - Kim, Kibeom (Ann Occup Environ Med, 2021)
BACKGROUND: Age-related macular degeneration (AMD) is the leading cause of blindness. Shift work has well-known adverse effects on health. However, few studies have investigated the relationship between shift work and AMD. This study was conducted to investigate the relationship between shift work and AMD. METHODS: This study used aggregated data from the 2010–2012 cycles of the Korea National Health and Nutrition Examination Survey. The work schedules were classified into 2 types: day work and shift work. AMD was determined using fundus photographs. The χ(2) test and multiple logistic regression analysis were used to assess sex-stratified relationship between shift work and AMD. RESULTS: The odds ratio (OR) of AMD in male shift workers was higher (1.54 [95% confidence interval, CI: 1.01–2.36]) than that in male day workers after adjusting for covariates. After dividing into subgroups of the shift work pattern, the OR of AMD in male night shift workers was higher (1.75 [95% CI: 1.07–2.85]) than that in male day workers after adjusting for covariates. However, results of the female worker group were not significant. CONCLUSIONS: The results of this study provide limited support for the hypothesis that shift work is related to AMD. Further prospective studies are needed to define the relationship between shift work and AMD.